Pengaruh Cara Pengolahan Terhadap Sifat Fisikokimia Pisang Tongka Langit (Musa troglodytarum) - Gilian Tetelepta; Josefina Talahatu; Syane Palijama (AGRITEKNO: Jurnal Teknologi Pertanian, 2015)
Tongka Langit banana (Musa troglodytarum) is one of the banana cultivar which is useful for health and has high nutrient content. It can be eaten raw and can be processed into various products. This research was aimed to study effect of tongka langit banana processing on its tannin content and other physicochemical changes result from those processes. A completely randomized design was used with five levels of treatment, i.e.: no processing, roasted tongka langit banana, fried tongka langit banana, boiled tongka langit banana, steamed tongka langit banana. Results showed that roasted tongka langit banana can reduce tannin content to the lowest of 0.155% and risen respectively by fried of 0.166%, boiled of 0.170%, and steamed banana of 0.171 %. Besides that, roasted tongka langit banana had sugar content of 9.49%, vitamin C of 2.76 mg, moisture content of 76.9%, ash content of 1.58% and pH value 5.2. Among all processing methods applied, roasted tongka langit banana resulted in better physichochemical properties.